2007
DOI: 10.17221/742-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameters of noodles made with various supplements

Abstract: Ugarčić-Hardi Ž., Jukić M., Koceva Komlenić D., Sabo M., Hardi J. (2007): Quality parameters of noodles made with various supplements. Czech J. Food Sci., 25: 151-157.The influence of various supplements (extruded maize, maize, defatted soy flour and maize/soy flour blends, lecithin and wheat straw) on the pasta quality has been examined. Noodles were prepared by means of conventional laboratory equipment. Common wheat flour supplemented with 1% lecithin powder, 20% extruded maize flour, 20% maize flour, 10% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Rayas-Duarte et al (1996) studied the effects of buckwheat, amaranth, and lupin flours on durum wheat spaghetti in terms of protein digestibility and also of their cooking and sensory quality. Ugarčić-Hardi et al (2007) examined in their test the influence of various supplements (extruded maize flour, maize, soya, maize or soya flour and their blends, lecithin and wheat straw) on the pasta quality. Those supplements fortify pasta either with minerals (zinc, iron, phosphorus, etc.…”
mentioning
confidence: 99%
“…Rayas-Duarte et al (1996) studied the effects of buckwheat, amaranth, and lupin flours on durum wheat spaghetti in terms of protein digestibility and also of their cooking and sensory quality. Ugarčić-Hardi et al (2007) examined in their test the influence of various supplements (extruded maize flour, maize, soya, maize or soya flour and their blends, lecithin and wheat straw) on the pasta quality. Those supplements fortify pasta either with minerals (zinc, iron, phosphorus, etc.…”
mentioning
confidence: 99%
“…Water was used to clean the palate. For the evaluation, a nine‐point scale was adopted, where one and nine represented the lowest and the highest intensity of each specific attribute (Ugarčić‐Hardi et al ., ). Panelists were also asked to judged overall acceptability using numerical scores from 1 to 9 (1 = dislike extremely and 9 = like extremely).…”
Section: Methodsmentioning
confidence: 97%
“…Ugarcic-Hardi, Jukic, Komlenic, Sabo, and Hardi (2007) found that lecithin could reduce the cooking loss of refined noodles. Ugarcic-Hardi, Jukic, Komlenic, Sabo, and Hardi (2007) found that lecithin could reduce the cooking loss of refined noodles.…”
Section: Ingredients Additionmentioning
confidence: 99%